مدى استخدام تكنولوجيا التعليم في تدريس مقرر الفيزياء لطلبة المرحلة الثانوية في بغداد - عتابي، شاكر محمود نصيف (Kulliyyah of Education, International Islamic University Malaysia, 2022)
Although technological innovations have the potential to dramatically change the way scientific investigations are conducted and greatly enhance science teaching and learning, their use is no more efficient than any other resource or innovation when effective research-based teaching practices are not followed. This research reviews integrating modern technology methods in teaching science in general and physics in particular, it provides many examples of the available technology products for physics education and the corresponding effective research. The research presented the directives of the National Union of Teachers of Science and Technology for the twenty-first century, which urges teachers to develop and implement science curricula that integrate appropriate technology and make science learning more efficient and effective through computers. This requirement has prompted countries to pay attention to education that contributes to the progress and development of nations to keep pace with technological developments in education and other areas of life. Evaluation processes must maintain interest in education to contribute to the development and reform of curricula to achieve the desired goals to suit people's aspirations and raise the quality of education by providing a better picture to decision makers of the educational reality.. The study aims to find out "the extent of the use of educational technology in teaching physics to secondary school students in Baghdad" from the point of view of the (203) students of the sixth scientific grade. The researcher used the descriptive-analytical method to answer the study's questions. The SMARTPLS statistical tool was used to analyze the questionnaire data. The researcher found some shortcomings in some of the objectives of applying educational technology in physics, especially concerning the provision of modern technological equipment for school laboratories, or the use of some types of modern technology applications in teaching such as a computer. The researcher also recommended the necessity of adding modern and advanced technological topics to the content of school physics curricula, and integrating the theoretical and practical aspects, in order to achieve the comprehensive quality standards of textbooks on the one hand, and on the other hand, adding to the student modern and advanced scientific information that helps him to understand deeper and more accurately with the help of a specialized and qualified teaching staff.